Immune checkpoint inhibitor–associated myocarditis: manifestations and mechanisms - Moslehi, Javid; Lichtman, Andrew H.; Sharpe, Arlene H.; Galluzzi, Lorenzo; Kitsis, Richard N. (The Journal of clinical investigation, 2021)
Immune checkpoint inhibitors (ICIs) have transformed the treatment of various cancers, including malignancies once considered untreatable. These agents, however, are associated with inflammation and tissue damage in multiple organs. Myocarditis has emerged as a serious ICI-associated toxicity, because, while seemingly infrequent, it is often fulminant and lethal. The underlying basis of ICI-associated myocarditis is not completely understood. While the importance of T cells is clear, the inciting antigens, why they are recognized, and the mechanisms leading to cardiac cell injury remain poorly characterized. These issues underscore the need for basic and clinical studies to define pathogenesis, identify predictive biomarkers, improve diagnostic strategies, and develop effective treatments. An improved understanding of ICI-associated myocarditis will provide insights into the equilibrium between the immune and cardiovascular systems.